Ecology of vella pseudocytısus subsp. Glabrata greuter ın the naâma regıon of Algerıa (Bangladesh Journal of Botany, 2025)
The present study investigates the floristic composition and ecological characteristics of the Vella pseudocytisus plant group in the Kasdir region. The study employed 87 floristic surveys using the Braun-Blanquet method during the 2020 spring flowering peak. Species abundance, dominance, and sociability were analyzed alongside ecological and anthropogenic gradients through Correspondence Analysis (CA) and Ascending Hierarchical Classification (AHC). A total of 57 species were recorded, representing 49 genera and 20 families, with Poaceae, Asteraceae, and Fabaceae being the most represented. The biological spectrum reveals a dominance of therophytes (53.2%), followed by chamaephytes (23.5%) and hemicryptophytes (22%). The prevalence of therophytes, suggests ongoing ecological disturbance and overgrazing. Chamaephytic and psammophytic species, such as Thymelaea microphylla and Astragalus armatus, highlight adaptations to harsh and gypsum-rich soils. Biogeographically, the flora shows a strong Mediterranean component (26%), followed by endemic (23%) and Saharo-Sindian elements (12%). Five distinct vegetation units were identified, each with diagnostic and differential species tied to specific ecological conditions. The CA results underscore the importance of species-environment relationships, with anthropogenic impact and soil salinity emerging as key structuring factors. The study concludes that the Vella pseudocytisus group is undergoing significant degradation due to aridity and human activity. Conservation efforts are urgently needed, including habitat protection and ecological restoration, to safeguard this unique phytogenetic heritage. This research contributes valuable insights into steppe biodiversity, species adaptation strategies, and the conservation of vulnerable arid-land ecosystems in North Africa.Bangladesh J. Bot. 54(4): 1035-1044, 2025 (December)